2020
DOI: 10.3390/su12166507
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Effect of Dining and Motivational Factors on Out-Of-Home Consumer Food Waste

Abstract: Approximately 12% of total food waste is generated at the hospitality and food service level. Previous research has focused on kitchen and storeroom operations; however, 34% of food waste in the sector is uneaten food on consumers’ plates, known as “plate waste”. The effect of situational dining factors and motivational factors on plate waste was analysed in a survey of 1001 New Zealand consumers. A statistically significantly greater proportion (p < 0.05) of participants reported plate waste if the meal wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
(81 reference statements)
0
2
0
Order By: Relevance
“…Based on social cognitive theory in the context of food waste, females were more cognitively advanced than males. Females more closely monitored the reduction of food waste, so they were more motivated [ 71 ]. This contributed to their identification of more motivational factors that could have had a positive effect on their behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Based on social cognitive theory in the context of food waste, females were more cognitively advanced than males. Females more closely monitored the reduction of food waste, so they were more motivated [ 71 ]. This contributed to their identification of more motivational factors that could have had a positive effect on their behavior.…”
Section: Discussionmentioning
confidence: 99%
“…In New Zealand, Miranda et al (2018) demonstrated that 84% of the restaurant consumers agreed to use the option of leftover food takeout but when faced with a half-eaten meal situation, only 5% of the consumers dared to exercise the option. Smith et al (2020) showed that more food on the plate was wasted if the meal was expensive, if the food consumption duration was longer and during dinner time. They further pointed out that consumers were largely motivated to reduce plate waste to save money and to contribute to social and environmental issues related to food, hence underlining the role of restaurants to motivate consumers to reduce plate waste when eating out.…”
Section: Theoretical Backgroundmentioning
confidence: 99%